1996
DOI: 10.1090/s0002-9939-96-03384-9
|View full text |Cite
|
Sign up to set email alerts
|

Every Cech-analytic Baire semitopological group is a topological group

Abstract: Abstract. Among other things, we prove the assertion given in the title. This solves a problem of Pfister.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(20 citation statements)
references
References 18 publications
0
19
0
1
Order By: Relevance
“…Quasicontinuous functions are selections of minimal usco and minimal cusco maps [7,[9][10][11][12]. They found applications in the study of topological groups [4,21,23], in the study of dynamical systems [5], in the study of extensions of densely defined continuous functions [17], etc. The quasicontinuity is also used in the study of CHART groups [22].…”
Section: Introductionmentioning
confidence: 99%
“…Quasicontinuous functions are selections of minimal usco and minimal cusco maps [7,[9][10][11][12]. They found applications in the study of topological groups [4,21,23], in the study of dynamical systems [5], in the study of extensions of densely defined continuous functions [17], etc. The quasicontinuity is also used in the study of CHART groups [22].…”
Section: Introductionmentioning
confidence: 99%
“…In 1957, Ellis [7] showed that every locally compact semitopological group is a topological group. In [6], Bouziad proved that everyCech-complete semitopological group is a topological group. Later Kenderov et al [9] proved that a strongly Baire semitopological group is a topological group.…”
Section: Introductionmentioning
confidence: 99%
“…Following [12], a function f from X to Z is called quasi-continuous at x 0 if for neighborhoods U and W of x 0 and f (x 0 ), respectively, there exists a nonempty open set V ⊆ U such that f (V ) ⊆ W. The function f is called quasi-continuous if it is quasi-continuous at each point of X. The notion of quasi-continuity plays an important role in the proof that some semi-topological groups are actually topological groups (see, e.g., [4,5,21]) and in the proof of some generalizations of Michael's selection theorem [7]. The notion of quasi-continuity is frequently used for establishing the existence of points of joint continuity of two variables functions.…”
Section: Introductionmentioning
confidence: 99%